2017
DOI: 10.5935/1806-6690.20170039
|View full text |Cite
|
Sign up to set email alerts
|

Productive and economic efficiency of carrot intercropped with cowpeavegetable resulting from green manure and different spatial arrangements

Abstract: -The aim of this study was to evaluate the agro-economic efficiency of intercropping carrot with cowpeavegetable in relation to the amounts of biomass of Calotropis procera (Ait.) R.Br. (known locally as flor-de-seda) incorporated into the soil, and to different spatial arrangements. The study was carried out under field conditions from August to November of 2014, at the Experimental Farm 'Rafael Fernandes' of the Rural Federal University of the Semi-Arid (RFUSA), in Mossoró, in the State of Rio Grande do Nort… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 8 publications
0
13
0
1
Order By: Relevance
“…In the planting area, a solarization was carried out in pre-planting, with transparent plastic for 30 days, to combat nematodes and phytoparasites at 0-10 cm soil depths, especially Meloidogyne spp. (Favacho et al, 2017).…”
Section: Methodsmentioning
confidence: 99%
“…In the planting area, a solarization was carried out in pre-planting, with transparent plastic for 30 days, to combat nematodes and phytoparasites at 0-10 cm soil depths, especially Meloidogyne spp. (Favacho et al, 2017).…”
Section: Methodsmentioning
confidence: 99%
“…All maximum values for partial land equivalent ratios of the component cultures (LER r and LER cv ) and for the land equivalent ratio of the intercropping system were greater than unity, meaning that there was a better use of environmental resources and of the area by the crops, and of the hand labor in the various operations such as application of inputs and cultural practices with the use of the roostertree in the studied treatments when compared with their respective monocultures, indicating there is a complementarity between crops and an agronomic/biological advantage in the intercropping (Costa et al, 2017;Favacho et al, 2017). Rezende et al (2005) working with the radish and lettuce intercropping established in two row spacings and three lettuce transplanting times, observed that the intercropped systems established at zero day (with spacing of 0.30 × 0.30 m) and at 14 days after lettuce transplanting (with spacing of 0.40 × 0.30 m) had the highest land equivalent ratios of 1.76 and 1.61, respectively.…”
Section: Agronomic/biological Efficiency Indicesmentioning
confidence: 95%
“…They concluded that investment in education and improvement in infrastructure was critical for improving TE. From agronomic efficiency perspective, Favacho et al (2017) and Appiah et al (2017) studied productive and economic efficiency of carrot yield response to green manure and different spatial arrangements in Brazil and Ghana respectively in experimental design setting. In the Brazilian study it was concluded that the use of Calotropis procera (flor-de-seda) as green manure is economically viable for the farmer when intercrop carrot with cowpea-vegetable.…”
Section: Related Studiesmentioning
confidence: 99%